The Used of Gamification on Student's Understanding About Transportation Mode in The Supply Chain - Hikmatullah, Hikmatullah; Handayati, Yuanita (Journal of Business and Management, 2020)
Abstract. In the early spring of 2020, most governments around the world have temporarily closed educational institutions to contain the spread of the COVID-19 pandemic. Due to the current condition, most universities  around the world change their system from conventional to online learning (e-learning). An alternative to a learning method that can be used in e-learning is gamification or game-based learning. The study aims to see the effect of the gamified method on learning outcomes related to transportation mode in the supply chain. The method is exploring the differences of student knowledge using methods built from the flow model, study- related flow inventory (WOLF-S) measurement. The study analyzed changes from pre-test to post-test, as a representation of learning outcomes, using t-test analysis. Furthermore, continue evaluating the significance of gamification, or suggested by the presence of flow, against adjusting the score using the Spearman’s correlation. Data analysis shows that there is a significant improvement in score test, and there is a positive correlation of gamification method against learning outcomes achievement. Using the flow theory and measured by study-related flow inventory (WOLF-S) has proven the gamification method is important in increasing in achieving learning outcomes. The WOLF-S score also has a positive correlation with a positive change in the score of learning outcomes. In general, the gamification design is can improve in achieving learning outcomes.Keywords: COVID-19; gamification; supply chain; transportation; WOLF-S